In Athena's camp : preparing for conflict in the information age - Arquilla, John; Ronfeldt, David F. (MR (Series) ;, 1997)
The information revolution--which is as much an organizational as a technological revolution--is transforming the nature of conflict across the spectrum: from open warfare, to terrorism, crime, and even radical social activism. The era of massed field armies is passing, because the new information and communications systems are increasing the lethality of quite small units that can call in deadly, precise missile fire almost anywhere, anytime. In social conflicts, the Internet and other media are greatly empowering individuals and small groups to influence the behavior of states. Whether in military or social conflicts, all protagonists will soon be developing new doctrines, strategies, and tactics for "swarming" their opponents--with weapons or words, as circumstances require. Preparing for conflict in such a world will require shifting to new forms of organization, particularly the versatile, hardy, all-channel network. This shift will prove difficult for states and professional militaries that remain bastions of hierarchy, bound to resist institutional redesign. They will make the shift as they realize that information and knowledge are becoming the key elements of power. This implies, among other things, that Mars, the old brute-force god of war, must give way to Athena, the well-armed goddess of wisdom. Accepting Athena as the patroness of this information age represents a first step not only for preparing for future conflicts, but also for preventing them